Influence of Compensation and Organizational Culture Analysis on Increasing Employee Motivation - Moh. Rolli Paramata; Deby R. Karundeng; Moh. Afan Suyanto; Hasanuddin Hasanuddin; Yakup Yakup (PT Mattawang Mediatama Solution, 2023)
The purpose of this research was to analyze the effect of compensation and organizational culture on increasing employee motivation at a paint company in Tangerang, Banten. The research design used in this study uses a quantitative approach that is associative, namely research that examines the causal relationship between the independent variables, namely compensation (X1) and organizational culture (X2) to the dependent variable, namely increasing employee motivation (Y1). Based on the results of data analysis that has been carried out in the first hypothesis (H1), which states that compensation has a positive and significant effect on increasing employee work motivation, the t-count value of 10,492 is greater than the t-table value, which is 1,677, testing the second hypothesis (H2), which states that organizational culture has a positive and significant effect on increasing employee motivation, the t-count value is 9,731 greater than the t-table value, which is 1,677, which means that compensation and organizational culture have a positive and significant effect on increasing employee motivation, while the R-square value obtained by 0.869 which states that the variables of compensation and organizational culture affect the increase in employee motivation by 86.90% and the remaining 13.10% is influenced by other variables.